Students use of the PSOE model to understand weather and climate. (2nd July 2016) - Brown, Patrick L.; Concannon, James
ABSTRACT: One tried-and-true way to hook students' attention and promote long-lasting understanding is to sequence science instruction in an explore-before-explain instructional sequence. In these lessons for the second through sixth grade band, elementary students investigate the interaction between "cold" and "hot" substances and density to understand how fluids interact in air (some weather phenomenon) and water (ocean currents). The student-based activities are suited to a research-based strategy called the PSOE (predict, share, observe, and explain) sequence of instruction.